A STUDY ON THE EUROPEAN FOX HUNTING: FROM THE PERSPECTIVE OF FABRIC THEORY - REFERRING TO THE EVOLUTION OF CIVILIZATION - Wang, Linlin; Chen, Liquan (ASEAN Journal of Sport for Development and Peace, 2024)
Fabric theory, also known as "process theory", refers to the fact that the society consists of interdependent groups and their interacting network throughout history. The macro society and micro individuals are inseparable. In this paper, the author analyzed the Nobel Elias’s "fabric theory" and the European fox hunting activity. The author shall use references, historical research, logic and other research methods, aiming to figure out the evolution process of civilization that European fox hunting implied. Besides, the author tried to the development of competitive sports and social sports in China. In this paper, through the study of the fabric theory to promote the development of civilization, fox hunting revealed the political violence of the British parliamentary system. Stokevis’s critique of Elias showed that: European civilization has achieved rationality. 2. Based on the fabric theory, China's competitive sports and social sports are the outcome of civilization change. Thus, while reading Elias' representative work ‘The Progress of Civilization’, combined with the study on European fox hunting, we can get insights into the evolution of European civilization through the fabric theory. In addition, owing to civilization development, we may reduce violence in sports, which is conducive to the construction of Chinese social sports and competitive sports tradition. Thus, the research could make contributions to the development of civilization.